Mecânica quântica supersimétrica - Strapasson, José Lauro [UNESP] (Universidade Estadual Paulista (Unesp), 2001)
Neste trabalho fizemos uma revisão dos princípios da mecânica quântica supersimétrica. Trabalhamos preferencialmente na descrição de Schrôdinger e representação das coordenadas. O estudo da mecânica quântica supersimétrica foi feito predominantemente em 1 dimensão embora tenha havido exceções. Durante essa dissertação abordamos o formalismo hamiltôniano na descrição de Schrôdinger

In this work we have written a review of the principies of supersymmetric quantum mechanics. We worked preferentially in the Schrodinger picture and in the coordinate representation. The study of supersymmetric quantum mechanics was done predominantly in 1 dimension although there were some exceptions. During this dissertation we use the hamiltonian formalism in the Schrodinger’s picture
Keywords: Teoria quântica